The Effect of Fidgeting On Student Concentration Levels - Nugroho, K.A.; Kurnianingtyas, M.C.D. (Universitas Atma Jaya Yogyakarta, 2019)
Concentration is the ability needed to solve a problem.Â Students in learning also need concentration (DePorter et al., 2010). Unfortunately students have difficulty concentrating on doing a job. To help concentrate, students play pen, spin coins, play cellphones and other fun activities. To meet this goal, an agitated repellent device such as fidget spinner and fidget cube was made (Plafke, 2016). The benefits of spinner fidget for increasing concentration are still questionable (Schecter et al., 2017). Therefore, quantitative research is needed to prove the claim that fidget spinner can increase concentration. Unfortunately, there is currently no quantitative research that tests the effectiveness of these tools to increase short-term memory. The concentration level of a person can be measured using the Stroop test. Stroop tests utilize primitive cognitive operations, offering clues to the basic process of attention. The variable studied is Reaction Time for Correct Answer (RTCA), which is the amount of reaction time in answering correctly divided by the number of correct answers. The results of this study are the use of fidget spinner not having a significant effect on differences in the results of measurement of RTCA. The use of fidget spinner does not provide a significant difference in average error between not using fidget spinner and using fidget spinner.